Heroes masked and mythic - Wood, Christopher (McFarland & Company, Inc., Publishers, 2021)
Epic battles, hideous monsters and a host of petty gods–the world of Classical mythology continues to fascinate and inspire. Heroes like Herakles, Achilles and Perseus have influenced Western art and literature for centuries, and today are reinvented in the modern superhero. What does Iron Man have to do with the Homeric hero Odysseus? How does the African warrior Memnon compare with Marvel's Black Panther? Do DC's Wonder Woman and Xena the Warrior Princess reflect the tradition of Amazon women such as Penthesileia? How does the modern superhero's journey echo that of the epic warrior? With fresh insight into ancient Greek texts and historical art, this book examines modern superhero archetypes and iconography in art, comics, and film as the crystallization of the hero's journey in the modern imagination
Keywords: Heroes / Mythology; Comic books; strips; etc / History and criticism; Superheroes / Comic books; strips; etc; Archetypes in literature; Heroes in popular culture; Mythology / Comic books; strips; etc; Mythology; Classical; in literature; Rezeption; Comic; Mythologie; Antike; Superheld